A new time-scale for ray-finned fish evolution. - Hurley, I; Mueller, R; Dunn, K; Schmidt, E; Friedman, M; Ho, R; Prince, V; Yang, Z; Thomas, MG; Coates, M (2007)
The Actinopterygii (ray-finned fishes) is the largest and most diverse vertebrate group, but little is agreed about the timing of its early evolution. Estimates using mitochondrial genomic data suggest that the major actinopterygian clades are much older than divergence dates implied by fossils. Here, the timing of the evolutionary origins of these clades is reinvestigated using morphological, and nuclear and mitochondrial genetic data. Results indicate that existing fossil-based estimates of the age of the crown-group Neopterygii, including the teleosts, Lepisosteus (gar) and Amia (bowfin), are at least 40 Myr too young. We present new palaeontological evidence that the neopterygian crown radiation is a Palaeozoic event, and demonstrate that conflicts between molecular and morphological data for the age of the Neopterygii result, in part, from missing fossil data. Although our molecular data also provide an older age estimate for the teleost crown, this range extension remains unsupported by the fossil evidence. Nuclear data from all relevant clades are used to demonstrate that the actinopterygian whole-genome duplication event is teleost-specific. While the date estimate of this event overlaps the probable range of the teleost stem group, a correlation between the genome duplication and the large-scale pattern of actinopterygian phylogeny remains elusive.